ETHNOMATHEMATICS: AN EXPLORATION OF GEOMETRIC SHAPES AND STRUCTURES IN THE “UMA LENGGEâ€ TRADITIONAL HOUSE - Ririn Fitriatunnisa; Intan Dwi Hastuti; Yuni Mariyati; Saba Mehmood (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2025)
This research aims to explore the geometric shapes and structures found in the Uma Lengge traditional house with a qualitative approach based on the ethnographic model. This research was conducted in Maria Village, Wawo Sub-district, which was chosen because of the existence of the Uma Lengge traditional house and its role in cultural preservation and the development of the tourism sector. The problem raised in this research is the lack of studies linking the architectural design of Uma Lengge with mathematical concepts, especially within the framework of ethnomathematics, which has the potential to provide new insights into the relationship between culture and science. Respondents were selected using a purposive sampling technique, including custodians, cultural experts, and conservationists who have in-depth knowledge of the history and construction of Uma Lengge. Data collection was conducted through direct observation, literature study, and in-depth interviews. Data analysis techniques include data reduction, data presentation, and verification to ensure the validity and reliability of research findings. The results show that the architectural design of Uma Lengge combines geometric concepts in flat and spatial shapes, including patterns of triangles, squares, rectangles, triangular prisms, cubes, blocks, and pyramid frustums. These geometric structures not only reflect beauty and function, but also reflect local wisdom in the use of traditional mathematical concepts. This research makes an important contribution in expanding the understanding of ethnomathematics as part of cultural heritage that can be integrated into the mathematics learning process. It is recommended to conduct more comprehensive follow-up research on the application of other mathematical concepts, as well as develop ethnomathematics-based learning modules to increase students' appreciation of mathematics in a cultural context.